Respuesta :

Step-by-step explanation:

I understand from the corrupted typing of the problem text that we have 2 functions :

h(x) = x² + 11

g(x) = sqrt(x - 2)

we are looking for (g○h)(0).

first of all, (g○h)(0) is the same as g(h(0)).

don't get in panic because of this one iteration sign.

it just means we are running the second function first, and use that result as argument for the first function. that's all.

so,

h(0) = 0² + 11 = 11

11 is now the argument for g(x).

g(11) = sqrt(11 - 2) = sqrt(9) = 3

(g○h)(0) = 3